Indonesian Values of Islamic Education in the Munggahan Tradition in Trimulyo Village - Firdausi, Fiyya Zahrotul; Yusuf, Muhammad (International Journal on Advanced Science, Education, and Religion, 2025)
Tradition encompasses all inherited cultural practices from the past that continue to hold significance within a specific region. One such tradition is the "Discharge Berth," commonly practiced by the residents of Trimulyo Village, Mataram District, Central Lampung Regency, as a way of welcoming the holy month of Ramadan. However, community perspectives on this tradition vary—some support it while others oppose it, each with their own reasons. This research employs a qualitative, descriptive approach to explore the values of Islamic education embedded in the Munggahan tradition of Trimulyo Village. Data were collected through field research involving observations, interviews, and documentation, with informants including religious leaders, community figures, and local residents. The study reveals that the Munggahan tradition reflects core Islamic educational values, including those related to faith (aqidah), worship (ibadah), ethics (akhlaq), and social relations (muamalah). These values are expressed through activities such as religious outreach via Javanese traditions, communal almsgiving through food sharing, prayers for deceased ancestors (reading tahlil and Yasin), and expressions of gratitude for the arrival of Ramadan.